The Role of Financial Ratios in Explaining Information Quality Using the Factor Analysis Approach - Akram Karimi; Roya Darabi; Mohammad Reza Poorfakharan; Hossein Moghadam (Iranian Journal of Accounting, Auditing & Finance)
This study aims to investigate and predict information quality ranking using factor analysis and artificial intelligence in firms listed on the Tehran Stock Exchange for nine years from 2011 to 2019. The independent variable used in this study is the financial criteria of the firm, and the dependent variable is the quality measurement criteria of accounting information, in which all criteria have been converted into a single variable according to the factor analysis method. The present study is considered empirical accounting research, and the artificial intelligence method has been used to test the research hypotheses. The results indicate that according to the variable selection method of artificial intelligence, neighbourhood analysis among performance variables, including "Accounts receivable to sales ratio criteria", "Firm size", "Financial risk", "Current assets to total assets ratio", and "Cost to Sales ratio ", firms have the highest correlation with information quality rating. Other results indicate that linear and nonlinear artificial intelligence methods can predict accounting information firms' quality ratings on the Tehran Stock Exchange. Due to the importance of financial information quality in financial reporting, and innovation of the present study is the simultaneous use of all information quality criteria and artificial intelligence to examine research hypotheses